Etika Komunikasi Visual Influencer Pariwisata - Zakaria Lantang Sukirno (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2020)
In tourism promotion, tourist destination visual attraction becomes a weapon to attract attention for tourism influencers through their social media. But visual ethical problem appears when photograph has been edited or manipulated by them. Thus, “what does visual communication ethic from influencer in tourism promotion like?”. This research based on concepts of utilitarian ethics, visual communication ethics, and tourism visual communication. For its methodology, this research uses positivistic paradigm, descriptive research, and utilitarian ethical evaluation method. Research findings obtained the quantification of harmful consequences and good consequences for tourism influencers photograph manipulation, and two alternative acts for tourism influencers visual communication ethics.